2020
DOI: 10.24093/awej/vol11no3.1
|View full text |Cite
|
Sign up to set email alerts
|

Saudi University Students’ Perceptions towards Virtual Education During Covid-19 Pandemic: A Case Study of Language Learning via Blackboard

Abstract: Following the spread of COVID-19, many parts of the world have fully shifted to virtual education. Issues regarding students' readiness for this mode of education have been the main concerns in countries where students are not used to virtual classes. This article presents a case study that investigated the perceptions of Saudi university students towards learning via Blackboard, during the unusual mode of delivering education caused by Covid-19. The aim was to identify the merits and challenges of online lear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
56
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 17 publications
12
56
2
1
Order By: Relevance
“…This study also agrees with Paudel (2020), who found that online learning reduced the cost and time required to travel to institutions. Students in this study were discovered to prefer synchronous over asynchronous modes of delivery, a finding similar to that of other studies (Alnofaie, 2020;Bao, 2020;Mishra et al, 2020;Zgheib et al, 2019). The benefit mentioned in this study for this delivery learning mode included reduced virtual isolation for online learners (Akarasriworn & Ku, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study also agrees with Paudel (2020), who found that online learning reduced the cost and time required to travel to institutions. Students in this study were discovered to prefer synchronous over asynchronous modes of delivery, a finding similar to that of other studies (Alnofaie, 2020;Bao, 2020;Mishra et al, 2020;Zgheib et al, 2019). The benefit mentioned in this study for this delivery learning mode included reduced virtual isolation for online learners (Akarasriworn & Ku, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Mukhtar and Mukhtar (2020) found that the majority of students had access to reliable Internet services at their homes and that they were satisfied with the transition to online learning. Another study by Alnofaie (2020) found that language students prefer the asynchronous mode of delivering classes versus the synchronous mode due to flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the students reported that Blackboard helps to get course content, helps to do tasks & assignments, and helps to obtain the study material as Word, PDF, PowerPoint, audio, and video files. This result is consistent with Alokluk (2018) and Al-Nofaie (2020), who reported that most of the students are comfortable with things like getting materials, doing searches, and downloading files. However, some students reported problems downloading the course content, and uploading homework and assignments.…”
Section: Discussionsupporting
confidence: 88%
“…All these universities had taken up mainly Blackboard® as the primary learning management system (LMS), if only one, at the time of closure of HEIs in Saudi Arabia (Aljuhney & Murray, 2016;Al-Nofaie, 2020). All this wherewithal, namely technological and organizational resources, has mitigated the swift switchover to Emergency Remote Learning (ERL), although some obstacles, particularly the bandwidth issues and the Internet speed, especially in remote areas, and availability of laptops and tablets to students (AlHazizi, 2020), have occurred in the way.…”
Section: Introductionmentioning
confidence: 99%